Network + study guide : - Groth, David (Wiley, 2005)
CompTIA's popular Network+ certification will soon be upgraded to cover advances in networking technology. Here is the only self-study package for the Network+ exam that combines comprehensive instructional material with sophisticated network and operating system simulation software. And it comes to you at a tremendous value (less than the retail value of the simulation software alone)! With this premium product, you get the leading CAQC approved Network+ Study Guide which provides in-depth coverage of all official objectives plus two valuable CDs